Kajian perbandingan bentuk dan ragam hias batu nisan di kepulauan pantai timur Sabah - Mohammad Pu'ad Bebit; Ismail Ibrahim; Mohamad Azareen Aminullah; Teddy Marius Soikun (Universiti Malaysia Sabah, 2007)
NO ABSTRACT